2011
DOI: 10.4236/opj.2011.12009
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Inclusion Behavior of Amphiphilic p-Sulfonatocalix[4]arene with Ascorbic Acid by Spectrofluorometric Titrations

Abstract: The aqueous solution of tetrabutyl ether derivatives of p-sulfonatocalix[4]arene (SC4Bu) and ascorbic acid (AA) complex has been studied based on fluorescence and <sup>1</sup>H NMR spectroscopic results. It was found that the fluorescence intensity of SC4Bu quenched regularly upon the addition of AA. A 1:1 stoichiometry for the complexation was established and was verified by Job’s plot. The temperature-dependent inclusion constants were calculated, form which Δ H and ΔS values were calculated. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In particular, there is an established evidence base confirming that water-soluble calix[n]arenes which possess sulfonate groups in the 4-position on the upper rim are capable of solubilising drug molecules which otherwise possess poor solubility in aqueous media [9][10][11][12][13][14][15][16][17][18][19][20][21]. However, few investigations into the properties and utility of simple calix[4]resorcinarenes which bear sulfonate groups in the 2-position on the upper rim have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there is an established evidence base confirming that water-soluble calix[n]arenes which possess sulfonate groups in the 4-position on the upper rim are capable of solubilising drug molecules which otherwise possess poor solubility in aqueous media [9][10][11][12][13][14][15][16][17][18][19][20][21]. However, few investigations into the properties and utility of simple calix[4]resorcinarenes which bear sulfonate groups in the 2-position on the upper rim have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A derivative of para-sulfonatocalix [4]arene bearing tetrabutyloxy groups in place of the hydroxyl groups on the lower rim was shown to form a stoichiometric complex with ascorbic acid in water [54]. Interestingly the association constant, determined by fluorescence spectroscopy, increased dramatically as the temperature of the solution increased, indicating that entropy plays a significant role in determining the degree of complexation.…”
Section: Sulfonatocalix[n]arenes For Drug Solubilizationmentioning
confidence: 92%
“…Interestingly the association constant, determined by fluorescence spectroscopy, increased dramatically as the temperature of the solution increased, indicating that entropy plays a significant role in determining the degree of complexation. NMR studies demonstrated that the ascorbic acid molecule was complexed such that the hydroxylated chain was embedded within the hydrophobic cavity, leaving the unsaturated lactone moiety projected out of the cavity facilitating the formation of a hydrogen-bonded network with the sulfonate functional groups [54].…”
Section: Sulfonatocalix[n]arenes For Drug Solubilizationmentioning
confidence: 99%